Polyethylene glycol (PEG) decorated graphene oxide nanosheets for controlled release curcumin delivery - Charmi, Jalil (Heliyon, 2019)
Nowadays, the use of nanostructures in various medical and biological fields such as drug delivery in cancer treatment is increasing. Among the nanostructures, graphene oxide (GO) is an excellent candidate for drug delivery application because of its unique properties. For more stability, GO can bind with various polymers by its carboxyl, hydroxyl and epoxy functional groups. In this study, firstly GO synthesized by the improved Hummers chemical method and then polyethylene glycol polymer was conjugated to it by using EDC/NHS catalyst. Finally, curcumin (Cur) as anti-cancer drug has been loaded onto the PEGylated graphene oxide (GO-PEG). Next, curcumin loaded onto PEGylated graphene oxide (GO-PEG-Cur) were evaluated by using ultraviolet, Fourier transform infrared spectroscopy, differential scanning calorimeter, atomic microscopic force and dynamic light scattering. The amount of loaded drug was calculated about 4.5% with the help of the standard curcumin curve and UV/Vis spectrometer. Also, the result of release shows that maximum drug release rate for this nanocarrier in pH 5.5 and 7.4 was measured 50% and 60%, respectively, after 96 hours. The results showed that the zeta-potential analysis of GO-PEG-Cur was about -13.9 mV that expresses a negative surface charge for produced nanocarrier.